2016
DOI: 10.1007/s11356-016-8197-5
|View full text |Cite
|
Sign up to set email alerts
|

Photodegradation of ethylene by use of TiO2 sol-gel on polypropylene and on glass for application in the postharvest of papaya fruit

Abstract: The papaya is a commercially important fruit commodity worldwide. Being a climacteric fruit, it is highly perishable. Thus, for the transportation of papaya fruit for long distances without loss of quality, it is necessary to avoid the autocatalytic effect of ethylene in accelerating the ripening of the fruit. This work addresses the application of heterogeneous photocatalysis to the degradation of ethylene. A TiO sol-gel supported on polypropylene (PP) and on glass was used as the catalytic material, and a UV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 37 publications
1
2
0
2
Order By: Relevance
“…This was evident from the colour parameter data obtained and presented in Table 2 . Similar observations were reported by Lourenço et al ( 2016 ) where the authors found that the skin of papaya exposed to radiation was darker than the fruit in control fruit. The discoloration of fruit during exposure to UV treatments has been associated with the type of radiation, light induced anthocyanin biosynthesis (Zhao et al 2017 ), and overdose of radiation (Ding et al 2014 ), that could lead to breakage of cellular membrane, increase enzyme -substrate contact and led to tissue color change (Sethi et al 2018 ).…”
Section: Changes Associated With Exposure Of Apples Alone To Direct Vuvsupporting
confidence: 90%
See 1 more Smart Citation
“…This was evident from the colour parameter data obtained and presented in Table 2 . Similar observations were reported by Lourenço et al ( 2016 ) where the authors found that the skin of papaya exposed to radiation was darker than the fruit in control fruit. The discoloration of fruit during exposure to UV treatments has been associated with the type of radiation, light induced anthocyanin biosynthesis (Zhao et al 2017 ), and overdose of radiation (Ding et al 2014 ), that could lead to breakage of cellular membrane, increase enzyme -substrate contact and led to tissue color change (Sethi et al 2018 ).…”
Section: Changes Associated With Exposure Of Apples Alone To Direct Vuvsupporting
confidence: 90%
“…Lourenço et al ( 2016 ) investigated the effect of UV radiation treatment on the colour of papaya fruit at room temperature. The results showed that the fruit exposed to UV radiation had lower L * value compared to untreated fruit.…”
Section: Changes Associated With Exposure Of Apples Alone To Direct Vuvmentioning
confidence: 99%
“…Pada tahun 2018 metode sol-gel berkembang pada sintesis Lithium Mangan Oksida Spinel (LiMn2O4) dengan serangkaian silicon melalui proses sol gel, hasil XRD menunjukkan bahwa sampel silicon yang didoping dapat mempertahankan struktur spinel dari LiMn2O4.LiMn2O4 (Huang et al, 2018). Metode sol-gel merupakan metode yang digunakan untuk membuat suatu material padat dari nonopartikel atau molekul yang berukuran kecil terutama digunakan untuk fabrikasi dari oksida logam seperti silikon (Si) dan titanium (Ti) (Lourenço et al, 2016). Metode ini dapat digunakan untuk membuat komposit ZnO/SiO2 berbahan dasar limbah seng dan abu vulkanik dimana komposit ini dapat digunakan untuk mendegradasi zat warna pada limbah industri tekstil.…”
Section: Pendahuluanunclassified
“…To reduce the postharvest loss and delay the ripening, several postharvest technologies have been used for minimizing or inhibiting the action of ethylene. Among then, 1-methylcyclopropene (1-mcp) (Amornputti et al, 2016; Balaguera-López et al, 2017; Rizzolo et al, 2014; Rupavatharam et al, 2015), ozone (Minas et al, 2010; Skog and Chu, 2001), UV-A/UV-C light (Artés-Hernández et al, 2010; Imaizumi et al, 2018; Lourenço et al, 2016), and modified atmosphere (Belay et al, 2019; Fagundes et al, 2015; Giuggioli et al, 2015). However, all those technology has been showed limitations.…”
Section: Introductionmentioning
confidence: 99%